Cáncer parental: díptico de soporte para padres y madres recién diagnosticados - Fuentes Sanmartín, Sònia; Barez Villoria, Milagros; Caba Vela, Lydia; De Cáceres Zurita, María Luisa (Psicooncología, 2018)
Nota informativa.